Human Cytomegalovirus Upregulates Expression of HCLS1 Resulting in Increased Cell Motility and Transendothelial Migration during Latency. - Aslam, Yusuf; Williamson, James; Romashova, Veronika; Elder, Elizabeth; Krishna, Benjamin; Wills, Mark; Lehner, Paul; Sinclair, John; Poole, Emma (Elsevier, 2019)
Human cytomegalovirus establishes a lifelong, latent infection in the human host and can cause significant morbidity and mortality, particularly, in immunocompromised individuals. One established site of HCMV latency and reactivation is in cells of the myeloid lineage. In undifferentiated myeloid cells, such as CD14+ monocytes, virus is maintained latently. We have recently reported an analysis of the total proteome of latently infected CD14+ monocytes, which identified an increase in hematopoietic lineage cell-specific protein (HCLS1). Here we show that this latency-associated upregulation of HCLS1 occurs in a US28-dependent manner and stabilizes actin structure in latently infected cells. This results in their increased motility and ability to transit endothelial cell layers. Thus, latency-associated increases in monocyte motility could aid dissemination of the latently infected reservoir, and targeting this increased motility could have an impact on the ability of latently infected monocytes to distribute to tissue sites of reactivation.
Keywords: Cellular Physiology; Immunology; Virology